Customer Loyalty To The Sharia Microfinance Institution In Indonesia - Shodiq, Abdullah (ITB AAS INDONESIA Surakarta, 2023)
Various studies have identified the correlates of customer loyalty including satisfaction, trust, commitment, involvement, perceived cost, and service quality. This paper aims to describe customer loyalty to the Sharia microfinance institution in Indonesia. The main question developed was whether the customers of this institution have similar drives in maintaining their loyalty in using its services. The study uses qualitative method with a phenomenological approach and descriptive analysis. Data were collected from a series of interviews and focus group discussions with the management and the customers of Bayt al Mal wa al Tamwil Maslahah (BMTM) Sidogiri Pasuruan Indonesia. The study found that customer loyalty to BMTM Sidogiri was characterized by a positive response to and the utilization of products. The positive attitude towards BMTM products was based on the motives of meeting daily needs, business development and the acceptance of sharia values in the form of blessing and economic justice when using the products. In addition, the customer loyalty to BMTM Sidogiri was driven by emotional connection among the alumni of Sidogiri pesantren even though there is no structural connection between BMTM and Sidogiri pesantren. In maintaining its customer loyalty, the BMTM Sidogiri attempts to bring its services closer to the community, opens BMTM branches in other cities and adds new counters to ease customer transaction services. This study suggests that the customer loyalty to the Islamic financial institution is determined by a combination of shariah values acceptance and the fulfilment of daily need as well as business development